PENERAPAN MODEL 7E (ELICIT, ENGAGE, EXPLORE, EXPLAIN, ELABORATED/EXTEND, AND EVALUATE) LEARNING CYCLE) PADA PELAJARAN FISIKA DALAM IMPLEMENTASI KURIKULUM 2013 - Siti Ani Apriyani; Karlina Arti Suprapto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
The main purpose of this literature study is determine the suitability of the 7E models learning cycle in high school, physics lessons, in the implementation of Curriculum 2013. The 7E learning cycle model begins with Elicit which means the child is directed to give attention to new things or old things that never care before. The next stage is Engage, at this stage the child is directed to focus on a specific topic. This model was followed by directing children to be able to examine more deeply the topic, Explore. If the student is considered capable understand the topic, then the student will easily explain the topic in brief, both verbally and in writing, Explain. The next stage Elaborate / Extend, the stage had to be marked with the student's inability to explain the understanding obtained on their friends and share information obtained. Highest stages in this model is Evaluate, formal and informal summative stage where the child is considered to have really understood the topic. By using this model the child should be able to understand and make the subject as a means of understanding that will always be remembered. Thus, this model is considered to be capable of meeting the demands Kurikulim 2013, which expects the output of a meaningful lesson. Keywords: Elicit, Engage, Explore, Explain, Elaborate/Extend, Evaluate .